Active macromolecules of honey form colloidal particles essential for honey antibacterial activity and hydrogen peroxide production - Katrina Brudzynski (Nature Portfolio, 2017)
Abstract Little is known about the global structure of honey and the arrangement of its main macromolecules. We hypothesized that the conditions in ripened honeys resemble macromolecular crowding in the cell and affect the concentration, reactivity, and conformation of honey macromolecules. Combined results from UV spectroscopy, DLS and SEM showed that the concentration of macromolecules was a determining factor in honey structure. The UV spectral scans in 200–400 nm visualized and allowed quantification of UV-absorbing compounds in the following order: dark > medium > light honeys (p < 0.0001). The high concentration of macromolecules promoted their self-assembly to micron-size superstructures, visible in SEM as two-phase system consisting of dense globules distributed in sugar solution. These particles showed increased conformational stability upon dilution. At the threshold concentration, the system underwent phase transition with concomitant fragmentation of large micron-size particles to nanoparticles in hierarchical order. Honey two-phase conformation was an essential requirement for antibacterial activity and hydrogen peroxide production. These activities disappeared beyond the phase transition point. The realization that active macromolecules of honey are arranged into compact, stable multicomponent assemblies with colloidal properties reframes our view on global structure of honey and emerges as a key property to be considered in investigating its biological activity.